Lipid changes in Duchenne muscular dystrophy - Hughes, B. P. (1972)
Thin layer chromatographic analysis of lipid extracts of rectus abdominis and gastrocnemius muscles from controls and patients with severe sex-linked Duchenne muscular dystrophy shows the dystrophic tissue to contain more sphingomyelin, less lecithin plus choline plasmalogen, and more total cholesterol than normal. Comparison of normal, dystrophic, and immature muscle suggests that these observations can be interpreted as showing a similarity between dystrophic and immature muscle and in this respect human Duchenne dystrophy resembles hereditary muscular dystrophy in the mouse. Although sphingomyelin was present in apparently normal amount in muscle biopsies from patients with various other neuromuscular disorders, it was raised in two cases showing evidence of peripheral neuropathy.